2022
DOI: 10.1080/21655979.2022.2054913
|View full text |Cite
|
Sign up to set email alerts
|

The crystallin alpha B (HSPB5)-tripartite motif containing 33 (TRIM33) axis mediates myocardial fibrosis induced by angiotensinogen II through transforming growth factor-β (TGF-β1)-Smad3/4 signaling

Abstract: Myocardial fibrosis, a common pathological manifestation of cardiac remodeling (CR), often leads to heart failure (HF) and even death. The underlying molecular mechanism of the role of TRIM33 in Ang II–induced myocardial fibrosis is not fully understood. We found that TRIM33 was specifically upregulated in CFs and myocardial tissue after Ang II stimulation. Adult mice induced by Ang II were used as in vivo models, and Ang II–induced neonatal mouse primary cardiac fibroblasts (CFs) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The TRIM33 gene is on human chromosome 1p13 and belongs to a sub-family of chromatin binding TRIM proteins. The abnormal expression of TRIM33 is associated with the occurrence of human diseases, such as psoriasis ( 22 ), myocardial fibrosis ( 23 ) and types of cancer ( 24 ). The current study is the first, to the best of the authors' knowledge, to demonstrate that TRIM33 could suppress EC cell proliferation, migration and invasion and that these effects were dependent on inhibition of c-Myc, which is often highly expressed and serves pro-survival activity in cancer cells ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TRIM33 gene is on human chromosome 1p13 and belongs to a sub-family of chromatin binding TRIM proteins. The abnormal expression of TRIM33 is associated with the occurrence of human diseases, such as psoriasis ( 22 ), myocardial fibrosis ( 23 ) and types of cancer ( 24 ). The current study is the first, to the best of the authors' knowledge, to demonstrate that TRIM33 could suppress EC cell proliferation, migration and invasion and that these effects were dependent on inhibition of c-Myc, which is often highly expressed and serves pro-survival activity in cancer cells ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…After stimulation by angiotensinogen II (Ang II), the expression of TRIM33 was specifically fortified in primary cardiac fibroblasts and myocardial tissues of newborn mice. Overexpression of TRIM33 inhibited the fibrosis induced by Ang II in mice and accelerated cardiac repair, functional recovery, and restricted cardiac fibrosis 7 . TRIM33 was overexpressed in alveolar macrophages and fibroblasts in idiopathic pulmonary fibrosis patients and fibrotic lungs of rodents.…”
Section: Introductionmentioning
confidence: 95%
“…Overexpression of TRIM33 inhibited the fibrosis induced by Ang II in mice and accelerated cardiac repair, functional recovery, and restricted cardiac fibrosis. 7 TRIM33 was overexpressed in alveolar macrophages and fibroblasts in idiopathic pulmonary fibrosis patients and fibrotic lungs of rodents. TRIM33 gene knockout made mice sensitive to bleomycin (BLM)‐induced fibrosis, and AdCre‐TRIM33 inhibition aggravated BLM‐induced pulmonary fibrosis in mice.…”
Section: Introductionmentioning
confidence: 98%
“…[13] Furthermore, a series of in vivo and in vitro studies have confirmed that the dysregulation of circRNAs mediates the pathological processes of different diseases, including proliferation, apoptosis, oxidative stress, and inflammation. [14,15] Several reports have clarified the crucial role of circRNAs in the process of reperfusion damage. For example, circUCK2 expression is dysregulated after cerebral I/R, and overexpression of circUCK2 can reduce apoptosis during reperfusion damage.…”
Section: Introductionmentioning
confidence: 99%